Simulation study on performance of heating system with solar heat pump driven by gas engine - Hao, Hong; Wen, H.; Li, Y. (Editorial Department of Journal of Shenyang Jianzhu University, 2014)
Using renewable solar energy and natural gas for heating can not only alleviate energy crisis and decease environmental pollution, but also reduce the pressure of power grid. The author proposed a new type of heating system, based on solar heat pump driven by gas engine. Using TRNSYS and SIMULINK simulation, study on heating performance of the system was carried out. Influences of different parameters on system heating performance were also analyzed. Results show that the coefficient of performance(COP) of system is 4.76. The first usable energy efficiency can reach 1.96. When the RPM of gas compressor is 1 600~2 000 r/min, the heating system performance and the comfort are the best. It indicates that the solar energy heat pump driven by gas engine has obvious advantages in heating system stability, energy saving and economical effects compared with the traditional system of solar heat pump driven by electric motor.